2013
DOI: 10.1371/journal.pone.0056053
|View full text |Cite
|
Sign up to set email alerts
|

Long-Lasting Antidepressant Action of Ketamine, but Not Glycogen Synthase Kinase-3 Inhibitor SB216763, in the Chronic Mild Stress Model of Mice

Abstract: BackgroundClinical studies demonstrate that the N-methyl-D-aspartate (NMDA) receptor antagonist, ketamine, induces rapid antidepressant effects in patients with refractive major depressive disorder and bipolar depression. This rapid onset of action makes ketamine a highly attractive drug for patients, particularly those who do not typically respond to therapy. A recent study suggested that glycogen synthase kinase (GSK)-3 may underlie the rapid antidepressant action of ketamine, although the precise mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 48 publications
(59 reference statements)
4
69
1
3
Order By: Relevance
“…Similarly, while selective GSK-3 inhibitors produce antidepressant-like activity when given alone (Gould et al, 2004;KaidanovichBeilin et al, 2004), only short-term behavioral tests (30 min) were conducted in these studies. A more recent study reported that after selective GSK-3 inhibition alone, antidepressant effects were not observed after 24 h or 1 week (Ma et al, 2013). The latter results are consistent with our present finding that single acute doses of lithium or the selective GSK-3 inhibitor SB 216763 are not sufficient to produce a more prolonged phase of antidepressant-like effects.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Similarly, while selective GSK-3 inhibitors produce antidepressant-like activity when given alone (Gould et al, 2004;KaidanovichBeilin et al, 2004), only short-term behavioral tests (30 min) were conducted in these studies. A more recent study reported that after selective GSK-3 inhibition alone, antidepressant effects were not observed after 24 h or 1 week (Ma et al, 2013). The latter results are consistent with our present finding that single acute doses of lithium or the selective GSK-3 inhibitor SB 216763 are not sufficient to produce a more prolonged phase of antidepressant-like effects.…”
Section: Discussionsupporting
confidence: 93%
“…To determine whether combined administration of a lowdose GSK-3 inhibitor and ketamine would be sufficient to evoke synaptogenesis and antidepressant effects similar to Ket-1/Li-10, we tested the effects of a combination of Ket-1 plus 2.5 mg/kg of SB 216763 (Ket-1/SB-2.5), previously shown to be ineffective by itself in reducing immobility 24 h after injection (Ma et al, 2013). Statistical analysis revealed a significant effect of the combination treatment on immobility time in the FST (F2,23 ¼ 18.299, po0.0001).…”
Section: Sb 216763 a Selective Gsk-3 Inhibitor Mimicked Lithium's Pmentioning
confidence: 99%
“…In rodents, the CUS paradigms produces anhedonia, the loss of interest in normally pleasurable and rewarding activities, which are a core symptom of depression (Ma et al, 2013;Willner, Muscat, & Papp, 1992). As based upon the results of our sucrose preference test, the CUS paradigm used in this report induced anhedonia, as rats exposed to chronic stress consumed significantly lower amounts of sucrose (Figure 3a).…”
Section: Discussionmentioning
confidence: 62%
“…Ketamine was used as a positive control in all of the behavioral experiments. The dose used routinely (10 mg/kg) was previously shown to exert antidepressant effects in mice (Maeng et al, 2008;Ma et al, 2013;Antony et al, 2014).…”
Section: Fast-onset Antidepressant Effects Of 4-chlorokynurenine Behamentioning
confidence: 99%
“…and quantitatively very similar, to those of ketamine, which was tested in parallel using a well-established antidepressant dose for mice [10 mg/kg;Maeng et al (2008); Ma et al (2013)]. We confirmed that the antidepressant-like action of 4-Cl-KYN in the acute FST involves the glycine B site, since pretreatment with glycine prevented the effects at the same dose shown to increase concentrations of glycine in the brain (albeit by less than a 2-fold difference) and to reverse the behavioral effects of NMDA channel blockers (Trullas and Skolnick, 1990;Evoniuk et al, 1991;Javitt et al, 1999).…”
Section: Fast-onset Antidepressant Effects Of 4-chlorokynureninementioning
confidence: 99%